2021
DOI: 10.33448/rsd-v10i13.21255
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasites in wild and exotic animals from a Zoobotanical Park in Northeast of Brazil

Abstract: One of the obstacles for ex situ conservation of wild and exotic animals are the diseases that affect them in captivity and, among them, the endoparasitoses, which are very frequent. The objective of this study is to report the occurrence of endoparasites in the fecal samples of animals from the Arruda Câmara Zoobotanical Park, at João Pessoa, Paraiba State, Brazil, as well as to identify significant statistical differences between the percentages of each parasite species found. To this end, 66 fecal samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
2
4
1
3
Order By: Relevance
“…Among the zoological groups evaluated, birds and mammals were more parasitized than reptiles. This same pattern was detected by other authors (Batista et al, 2021;Mewius et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Among the zoological groups evaluated, birds and mammals were more parasitized than reptiles. This same pattern was detected by other authors (Batista et al, 2021;Mewius et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…These results differ from other analyzes carried out with this species, where Batista et al (2021) found only protozoans in the tapir samples, with a predominance of trophozoites and cysts of Balantidium sp., and non-sporulated oocysts of coccidia.…”
Section: Sapajus Libidinosuscontrasting
confidence: 99%
See 3 more Smart Citations